Research on Kinematics of Vehicle Vibration Test Benches Based on a 6-UPS Parallel Mechanism - Song Hao; Xu Liyou; Chen Xiaoliang; Zhang Shuai; Zhang Jingquan; Zhao Junfeng; Wang Jie (Jixie chuandong)
In order to improve the bearing performance and test accuracy of vehicle vibration test benches, a test bench which can simulate vehicle vibration environment in an all-round way is designed based on a 6-UPS parallel mechanism. Through the mechanism analysis and degree of freedom calculation of the 6-UPS parallel mechanism, the pose relationship between components is established, the kinematics equation of the bench is deduced, and the kinematic characteristics of the bench are studied. By establishing the simulation model of vehicle vibration test benches, the kinematic simulation analysis of the bench is carried out using Adams software, and the kinematic parameters of the bench are verified theoretically. The results show that the vehicle vibration test bench can move according to the predetermined trajectory, the simulation curve is smooth without mutation, and the designed bench can meet the expected performance indexes, which verifies the rationality of the bench design. This study lays a foundation for the dynamic analysis, control strategy research and optimization design of vehicle vibration test benches.